The 10-year impact of a ward-level quality improvement intervention in acute hospitals: a multiple methods study - Sophie Sarre; Jill Maben; Peter Griffiths; Rosemary Chable; Glenn Robert (National Institute for Health Research, 2019)
Background: The 'Productive Ward: Releasing Time to Care'™ programme (Productive Ward; PW) was introduced in English NHS acute hospitals in 2007 to give ward staff the tools, skills and time needed to implement local improvements to (1) increase the time nurses spend on direct patient care, (2) improve the safety and reliability of care, (3) improve staff and patient experience and (4) make structural changes on wards to improve efficiency. Evidence of whether or not these goals were met and sustained is very limited. Objective: To explore if PW had a sustained impact over the past decade. Design: Multiple methods, comprising two online national surveys, six acute trust case studies (including a secondary analysis of local audit data) and telephone interviews. Data sources: Surveys of 56 directors of nursing and 35 current PW leads; 88 staff and patient and public involvement representative interviews; 10 ward manager questionnaires; structured observations of 12 randomly selected wards and documentary analysis in case studies; and 14 telephone interviews with former PW leads. Results: Trusts typically adopted PW in 2008-9 on their wards using a phased implementation approach. The average length of PW use was 3 years (range < 1 to 7 years). Financial and management support for PW has disappeared in the majority of trusts. The most commonly cited reason for PW's cessation was a change in quality improvement (QI) approach. Nonetheless, PW has influenced wider QI strategies in around half of the trusts. Around one-third of trusts had impact data relating specifically to PW; the same proportion did not. Early adopters of PW had access to more resources for supporting implementation. Some elements of local implementation strategies were common. However, there were variations that had consequences for the assimilation of PW into routine practice and, subsequently, for the legacies and sustainability of the programme. In all case study sites, material legacies (e.g. display of metrics data; storage systems) remained, as did some processes (e.g. protected mealtimes). Only one case study site had sufficiently robust data collection systems to allow an objective assessment of PW's impact; in that site, care processes had improved initially (in terms of patient observations and direct care time). Experience of leading PW had benefited the careers of the majority of interviewees. Starting with little or no QI experience, many went on to work on other initiatives within their trusts, or to work in QI at regional or national level within the NHS or in the private sector. Limitations: The research draws on participant recall over a lengthy period characterised by evolving QI approaches and system-level change. Conclusions: Little robust evidence remains of PW leading to a sustained increase in the time nurses spend on direct patient care or improvements in the experiences of staff and/or patients. PW has had a lasting impact on some ward practices. As an ongoing QI approach continually used to make ongoing improvements, PW has not been sustained, but it has informed current organisational QI practices and strategies in many trusts. The design and delivery of future large-scale QI programmes could usefully draw on the lessons learnt from this study of the PW in England over the period 2008-18. Funding: This National Institute for Health Research Health Services and Delivery Research programme.